Review: Water quality in non-perennial rivers (with erratum) - Day, JA; Malan, HL; Malijani, E; Abegunde, AP (Water SA, 2019)
More than half the river-lengths of rivers in southern Africa dry up occasionally or – more commonly – seasonally. Here we review the literature on water quality (WQ) in non-perennial rivers (N-PRs), with emphasis on river management and southern African systems. Hydrological regimes cover a spectrum from relatively predictable and unvarying in perennial rivers, to unpredictable and highly variable in non-perennial rivers, which are complex, continually shifting mosaics of flowing water, standing-water pools and terrestrial habitats. N-PRs are uncommonly difficult to manage because they represent a limited source of water that is renewed unpredictably and is competed for by local people as well as being required by wildlife. Groundwater, and therefore its chemical and physical features, contributes significantly to base flow and to the maintenance of pools remaining in the bed when the river is not flowing. Water chemistry reflects catchment geology except in polluted systems. Salinity varies temporally, and spatially over three dimensions, and is the variable controlling the composition of the biotas of many N-PRs. Hydrological regimes are seldom predictable with any certainty; WQ varies naturally over time and space; groundwater often determines the WQ of surface water, especially in pools; and WQ in non-perennial rivers and pools may be affected by activities far upstream in the catchment. As yet we have no more than a sketchy understanding of the extent to which data on any one system can be applied to any other. Until we have a better understanding of these systems, the following basic principles should guide the management of WQ in N-PRs: (i) Rivers need to be assessed on a case-by-case basis. (ii) Understanding of the groundwater regime, including its chemistry, is crucial. (iii) Effluents need to be controlled by conservative effluent standards set for both ground and surface waters. (iv) Flows may need to be augmented at certain times of the year.